A Comparison Between Elzaki and Aboodh Transforms to Solve Systems of Linear Volterra Integral Equations (Journal of Humanitarian and Applied Sciences, 2019)
In this paper , the Elzaki transform is compared with Aboodh transform to solve some systems of linear Volterra integral equations.
Keywords: Elzaki transform; Aboodh transform; inear Volterra integral equations